2003
DOI: 10.1046/j.1525-1497.2003.21209.x
|View full text |Cite
|
Sign up to set email alerts
|

Health care of homeless veterans

Abstract: It is important to understand the needs of those veterans who are homeless. We describe characteristics of homeless male veterans and factors associated with needing VA benefits from a two-city, community survey of 531 homeless adults. Overall, 425 were male, of whom 127 were veterans (29.9%). Significantly more veterans had a chronic medical condition and two or more mental health conditions. Only 35.1% identified a community clinic for care compared with 66.8% of non-veterans ( P < .01); 47.7% identified a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 13 publications
2
45
1
Order By: Relevance
“…Estimates of the number of homeless men who are veterans vary, ranging from 18% to 49% in community samples, [5][6][7] with Vietnam era veterans continuing to be at higher risk for homelessness than other veteran cohorts. 6 Among those receiving homeless services, 33% of male clients were veterans, compared to 31% of men in the general population.…”
Section: Prevalence Of Chronic Homelessnessmentioning
confidence: 99%
“…Estimates of the number of homeless men who are veterans vary, ranging from 18% to 49% in community samples, [5][6][7] with Vietnam era veterans continuing to be at higher risk for homelessness than other veteran cohorts. 6 Among those receiving homeless services, 33% of male clients were veterans, compared to 31% of men in the general population.…”
Section: Prevalence Of Chronic Homelessnessmentioning
confidence: 99%
“…Homelessness is associated with significant health care needs and health complications, [1][2][3][4] often characterized by very high rates of emergency department use and inpatient hospitalizations [5][6][7] with an underutilizing of ambulatory care services. 8 Often the care provided can best be described as reactive to acute presentations: treating complications of homelessness such as frostbite or exposure-related illnesses; addressing acute complications of chronic conditions that are difficult to manage while homeless; and dealing with the consequences of untreated and undertreated mental health and substance abuse that often precipitate homelessness.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple prior studies have documented extensive use of emergency department and inpatient care by homeless individuals. [39][40][41][42] For example, Tsai and colleagues found that homeless Veterans had four times the odds of using EDs than non-homeless Veterans. 40 However, Gabrielian and colleagues noted that while HUD-VASH enrolled Veterans had initial significant increases in primary care and specialty utilization upon enrollment, HUD-VASH Veterans and low-income housed Veterans had similar likelihoods of medical/surgical inpatient and outpatient utilization compared with non-homeless peers over time.…”
Section: Discussionmentioning
confidence: 99%